2021
DOI: 10.52711/0974-360x.2021.00877
|View full text |Cite
|
Sign up to set email alerts
|

Prevalance and role of Melatonin on PCOS in its treatment using Herbal Drugs

Abstract: The polycystic ovarian syndrome is a convoluted endocrine disorder of the reproductive system which influences several girls with puberty and 6-8% of germinating women in endemic populations and displays a wide spectrum of clinical phenomenon. This disorder was first reported in 1935 as a synthetic clinical error for its associations with high androgen levels, hyperinsulinemia, and PCOS. The pineal hormone melatonin is known to regulate a mixture of central and peripheral actions related to circadian rhythms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…All the individuals were taking conventional medicines and a modi ed diet plan. However, the intervention group participants were taking 1000 mg/day of evening primrose oil for 10 weeks [30]. The participants were requested not to alter their routine physical activity and take any other nutritional supplement.…”
Section: Methodsmentioning
confidence: 99%
“…All the individuals were taking conventional medicines and a modi ed diet plan. However, the intervention group participants were taking 1000 mg/day of evening primrose oil for 10 weeks [30]. The participants were requested not to alter their routine physical activity and take any other nutritional supplement.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that melatonin supplementation may present great therapeutic potential for women with PCOS. [119,120] One newer randomized study explored technology in helping PCOS patients. This research demonstrated that a mobile health application program based on the Transtheoretical Model can lead to long-term reductions in BMI, waist circumference, anxiety, and depression, as well as improvements in exercise and diet adherence among patients with PCOS.…”
Section: New and Emerging Treatmentsmentioning
confidence: 99%
“…This suggests that melatonin supplementation may present great therapeutic potential for women with PCOS. [ 119 , 120 ]…”
Section: Managementmentioning
confidence: 99%